Effects of Enterocytozoon hepatopenaei infection on intestinal immune defense and physiological processes of Penaeus vannamei - Cao, Zheng; He, Chuanyu; Yin, Zhipeng; Chen, Caiyi; Li, Fan; Yan, Dongchun; Li, Ting; Chang, Linrui; Si, Lingjun (Frontiers in Marine Science, 2025)
As the main pathogen causing growth retardation, EHP is considered to be mainly parasitic in the hepatopancreas of shrimp. However, the intestines of shrimp infected with EHP frequently exhibit syndromes such as jejunum and white midgut. Therefore, the challenge experiment was carried out in this study to compare the differences in intestinal histology, digestion and absorption, immune defense and oxidative stress of P. vannamei between the control group and EHP infection group. Histological analysis showed that EHP infection significantly damaged the intestine of the shrimp, including intestinal villus rupture and outer membrane impairment. Concurrently, EHP infection can trigger intestinal immune response, and the expression of key immune genes like Toll, myeloid differentiation factor, anti-lipopolysaccharide factor, and Relish was significantly enhanced, while the expression of IMD and alkaline phosphatase was suppressed. Additionally, antioxidant genes manganese superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and nuclear factor E2-related factor 2 were up-regulated to varying extents in EHP infection group, and the contents of lipid peroxides and malondialdehyde were heavily accumulated. Moreover, the expression levels of key genes involved in nutrient absorption, transport and synthesis, such as glucose transporter 1, Na+-K+ATPase, fatty acid synthase, acetyl-CoA carboxylase, rapamycin kinase, mTOR regulation-related protein, eukaryotic translation initiation factor 4E binding protein, ribosomal protein S6 kinase, were significantly up-regulated. However, the activities of amylase, lipase, and trypsin were inhibited in EHP infection group throughout the experiment. In summary, EHP infection damaged the intestine of P. vannamei, accompanied by immune response and oxidative stress. At the same time, nutrient transport and synthesis pathways were activated, while digestive enzyme activities were inhibited, indicating that in order to maintain survival, shrimps must accelerate material transport. Unfortunately, it remains in a state of nutrient deficiency that ultimately affects growth.